Keanekaragaman karakteristik morfologi beberapa aksesi ubi jalar yang dibudidayakan oleh masyarakat Suku Irarutu dan Suku Dani di Kabupaten Kaimana - Yulianus Sinon, Johan; Mawikere, Nouke Lenda; Prabawardani, Saraswati; S. Sarungallo, Amelia; Wibawati, Zarima (Cassowary, 2025)
ABSTRACT : This research aims to identify the diversity of morphological characteristics of several sweet potato accessions cultivated by communities in the two tribes in the Kaimana Regency. The research was carried out in the Lower Arguni District in 5 villages (Coa, Afu Afu, Wetuf/Sawi, Kufuryai, Wermenu) inhabited by the Irarutu and Dani tribes (a local tribe from Wamena). The research used descriptive methods with survey, observation, and interview techniques. The research location was determined deliberately (purposive sampling) based on the local tribe population. The sweet potato in each village was also determined deliberately (purposive sampling) based on the number of accessions and different morphological characteristics. Observation of morphological characteristics included the morphology of stems or tendrils, leaves, and tubers. Data analysis was carried out using cluster analysis with pro- gram NTSYS-pc version 2.0. The morphological character similarity coefficient used is the simple matching coefficient. The research results showed that there was morphological diversity in 26 sweet potato accessions cultivated in five villages by the Irarutu and Dani tribes from Wamena. Diversity in morphological characteristics occurs in the characteristics of tendrils/stems, leaves, and tubers. Based on the results of the grouping analysis, the coefficient of similarity in morphological characteristics of the 26 sweet potato accessions was between 0.41 and 1, which means that the similarity in morphological characteristics was between 41% and 100%. The 26 sweet potato accessions were not grouped based on the village where they were grown but were grouped randomly. At the lowest similarity in morphological characteristics, namely 41%, 26 accessions were grouped into two groups, namely: group I consisted of 17 accessions, while group II consisted of 9 accessions. At the highest similarity, namely 100%, there are several accessions that group together, namely AfuAfu-6 and Wetuf-2; Coa-4, Afu Afu-7, Kufuryai-5; and Afu Afu-10, Wetuf-4, Kufuryai-1.